A CASE OF THROMBOSIS DUE TO PAROXYSMAL NOCTURNAL HAEMOGLOBINURIA PRESENTING AT AN EARLY AGE - Ain, Qurrat-ul-; Saleem, Huzaifa; Iqbal, Sarwat; Ghayas, Rabia (Journal of Ayub Medical College Abbottabad, 2018)
Paroxysmal Nocturnal Haemoglobinuria (PNH) is an acquired, rare life-threatening disorder characterised by compliment mediated hemolytic anemia, thrombosis and impaired bone marrow function. It occasionally presents in childhood or adolescence. This is a case of a 14-year old female presented with complaints of shortness of breath, palpitation and abdominal pain whose laboratory test results were consistent with Coomb's test negative haemolytic anaemia. Contrast enhanced Computed Tomography Scan (CT scan) of abdomen revealed splanchnic circulation thrombosis as well as partially occluding thrombus in the inferior vena cava. Flow cytometry showed loss of CD59 expression on erythrocytes confirming the diagnosis of paroxysmal nocturnal hemogloubinuria. Supportive treatment was given with haematinics, blood transfusions and anticoagulants. After that, hematopoietic stem cell transplantation was conducted successfully as a permanent treatment. PNH can present at an earlier age and therefore should be included in differential diagnosis of haemolytic anaemia. Keywords: Paroxysmal Nocturnal Hemoglobinuria; thrombosis; hematinic